c) C = 129 - 5 . [29 - (6 - 1)2]
C = 129 - 5 . (29 - 52)
C = 129 - 5 . (29 - 25)
C = 129 - 5 . 4
C = 129 - 20
C = 109
Bài 1:
c) \(C=129-5\left(29-5^2\right)=129-5.4=129.20=109\)
Bài 2:
a) \(\Rightarrow3^x=3^2.3^3=3^5\Rightarrow x=5\)
b) \(\Rightarrow5x-4=2^3.2=8.2=16\)
\(\Rightarrow5x=20\Rightarrow x=4\)
a) 3x = 32 . 27
3x = 32 . 33
3x = 35
\(\Rightarrow\) x = 5
a) 3x = 32 . 27
⇒3x = 32 . 33
⇒ 3x = 35
⇒ x = 5
Bài 2:
a) ⇒3x=32.33=35
⇒x=5⇒
3x=32.33=35
⇒x=5
b) ⇒5x−4=23.2=8.2=16⇒5x−4=23.2=8.2=16
⇒5x=20⇒x=4
b) (5x - 4) : 2 = 23
(5x - 4) = 23 . 2
(5x - 4) = 24
5x - 4 = 16
5x = 16 + 4
5x = 20
x = 20 : 5
x = 4
c) C = 129 - 5 . [29 - (6 - 1)2]
C = 129 - 5 . (29 - 52)
C = 129 - 5 . (29 - 25)
C = 129 - 5 . 4
C = 129 - 20
C = 109
a) 3x = 32 . 27
3x = 32 . 33
3x = 35
=> x= 5
b) (5x - 4): 2 =23
5x - 4 = 8 . 2
5x - 4 = 16
5x = 16 +4
5x = 20
x =20 : 5 = 4